Taxonomy and conservation status of Tripogandra warmingiana (Seub.) Handlos (Commelinaceae), a previously obscure taxon from Brazil - Pellegrini, Marco Octávio De Oliveira; Aona-Pinheiro, Lidyanne Yuriko Saleme; Forzza, Rafaela Campostrini (Phytotaxa, 2013)
Tripogandra warmingiana is one of many poorly known and infrequently collected taxa of Commelinaceae in Brazil, and previously was known exclusively from the type collection and few historical collections from Minas Gerais. It is reported here for the first time for the states of Bahia and Rio de Janeiro, where it occurs exclusively in the Atlantic Rainforest, between 50–800 elev. A new description is provided to better characterize the species. A newly revised key for the Brazilian species of the genus is presented that includes the new data presented here for T. warmingiana and some overlooked species. Commentaries on IUCN conservation status are also presented.